MiR-155 promotes cadmium-induced autophagy in rat hepatocytes by suppressing Rheb expression - Hui Zou (Elsevier, 2021)
Cadmium is an environmental pollutant that threatens the health of both humans and animals. Current studies have shown that while hepatotoxic damage induced by cadmium is closely related to autophagy, its intrinsic mechanism has not been elucidated. MicroRNA plays a regulatory role on different stages of autophagy. In this study, we investigated the mechanisms by which microRNA-155 (miR-155) regulate cadmium-induced hepatotoxicity in rat hepatocytes (BRL 3A cells) and in vivo. We found that cadmium exposure could cause liver injury in rats, resulting in a decreased liver index, increased alanine aminotransferase (ALT), aspartate aminotransferase (AST) and alkaline phosphatase (ALP) activity, hepatocyte steatosis, and ultrastructure damage. Cadmium exposure also induced autophagy in hepatocytes, resulting in increased expression of ATG5, Belin1, LC3II, and an increased number of autophagosomes. In addition, cadmium exposure upregulated miR-155 expression, downregulated Rheb mRNA expression, and downregulated the level of protein expression in the Rheb/mTOR signaling pathway in rat hepatocytes. The overexpression of miR-155 followed by cadmium exposure upregulated the level of autophagy in BRL3A cells, whereas miR-155 inhibition had the opposite effect. In addition, miR-155 negatively regulated Rheb. A dual-luciferase reporter assay verified the negative regulatory effect of miR-155 on Rheb targeting. Knockdown of Rheb downregulated cadmium-induced autophagy. Therefore, the Rheb/mTOR signaling can negatively regulate autophagy. The present study demonstrates that miR-155 promotes cadmium-induced autophagy in rat hepatocytes by suppressing Rheb expression.